Episodic Memory Impairment Mediates the Loss of Awareness in Mild Cognitive Impairment - Gagliardi, Geoffroy; Vannini, Patrizia (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Loss of awareness is a common symptom in Alzheimer’s Disease (AD) and is responsible for a significant loss of functional abilities. The mechanisms underlying the loss of awareness in AD is not known, although previous findings have implicated dysfunction of primary executive functioning (EF) or episodic memory (EM) to be the cause. Therefore, our main study objective was to explore the involvement of EF and EM dysfunction in loss of awareness across the clinical spectrum of AD. METHODS: A total of 895 participants (362 clinically normal [CN], 422 people with mild cognitive impairment [MCI] and 111 with dementia) from the Alzheimer’s Disease Neuroimaging Initiative was used for the analyses. A sub-analysis was performed in 202 participants who progressed in their clinical diagnosis from CN to MCI or MCI to dementia as well as dementia patients. Mediation models were used in each clinical group with awareness (assessed with the Everyday Cognitive function questionnaire) as a dependent variable to determine whether EF and/or EM would mediate the effect of amyloid on awareness. We also ran these analyses with subjective and informant complaints as dependent variables. Direct correlations between all variables were also performed. RESULTS: We found evidence for a decline in awareness across the groups, with heightened awareness in the CN and decreased awareness observed in the MCI and dementia group. Our results showed that EM, and not EF, partially mediated the relationship between amyloid and awareness so that greater amyloid and lower EM performance was associated with lower awareness. When analyzing each group separately, this finding was only observed in the MCI and in the group containing progressors and dementia patients. When repeating the analyses for subjective and informant complaints separately, the results were replicate only for the informant’s complaints. DISCUSSION: Our results demonstrates that EM decline, and less so EF, mediates the effect of amyloid on awareness. In line with previous studies demonstrating the development of anosognosia in the prodromal stage, our findings suggest that decreased awareness is the result of an inability for the participant to update his/her insight of his/her cognitive performance (i.e., demonstrating a petrified self).